Do contraste à analogia, intervenção numa ruína em Mondrões - António Pedro Santana Rebelo (2016)
This thesis was motivated by a personal concern related to desertification and aging of the population of rural areas, particularly of Mondrões, in the district of Vila Real, and the consequent loss of their social, economic and cultural significances,. A process which led to the tampering of its essence, through the anachronistic (re) construction and touristification of its territory. One proposes a reflexive exercise concerning the impactful issues on this part of the territory as well as its architecture, culminating with a proposal for a vernacular ruin from the eighteenth century, which is presented in this exercise as an exemplary case of study.